EVALUASI SISTEM INFORMASI PENDAFTARAN RAWAT JALAN BPJS DENGAN METODE PIECES RSUD SIDOARJO - Firdaus Sholehah; Ervina Rachmawati; Andri Permana Wicaksono; Alia Chaerunisa (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2021)
Medical records are said as good if there is a complete information to support orderly administration inimproving health services. The quality of hospital service is seen not only in the completeness of medicalrecords but also in the accuracy, speed, and accuracy of hospital management information systems. Basedon a preliminary study taken at Sidoarjo district medical records installation, it was known that in theapplication of hospital management information systems there was a problem complained about by officials.One of the efforts to minimize these problems is to evaluate the system using the PIECES method(Performance, Information, Economics, Control, Efficiency, Service). This study aimed to analyze theperformance of BPJS outpatient registration information systems in RSUD Sidoarjo based on 6 aspects ofPIECES namely performance, information, economics, control, efficiency, and service. This type of researchwas qualitative. The method of data collection used was the interview and observation of the two enlistmentofficers. From the results of study obtained information that Information systems performance based onperformance aspects of Information Systems, it already runs fit with the user needs even though there wasan incomplete menu; information aspects, the information generated was quite accurate; economicsaspects, it had not produced an economic value, the hospital management information could not bridgingwith other information systems; control aspects, it already runs with the control of each user access andsecurity system provide passwords and usernames; efficiency aspects, it already provides efficiencies in itsapplication; service aspects, it already gives ease of use for the users. Based on the results of this evaluationit is expected that the Regional Hospital may complete the system information menus and conduct an MOUwith the BPJS Health for integrating the hospital management information with the BPJS Health’s V-Claim.